Digital Surveillance of Health and Safety Hazards at Tourist Attractions in Bali: First Preliminary Evidence - Wirawan, I Md Ady; Putri, Wayan Citra Wulan Sucipta; Sanjaya ER, Ngurah Agus; Hendrayana, Made Agus; Kurniasari, Ni Made Dian; Mulyawan, Ketut Hari (E-Journal of Tourism; Volume 7 Number 1 (March 2020)DO - 10.24922/eot.v7i1.59123, 2020)
This study examined the feasibility of conducting digital surveillance of health and safety hazards through a system that can be accessed by travelers using their mobile phones. A progressive mobile website and a mobile application were developed employing a research database which consists of hazards, risks and health facilities that have been geo-tagged and mapped based on their respective geographical positions in 197 tourist attractions in Bali. The system was launched in 80 strategic tourist attractions in Bali at the end of August 2019. Trends in some specific diseases, hazards, and risks were observed monthly using a keyword analysis. Serial data for the first four months were analyzed and presented descriptively. The result shows that in total there were 19,869 visits to the website, or an average of 163 visits per day. There has been a nearly three-fold increase in total website traffic from 85.2 in September to 245.8 in December 2019. Safety hazard is the most frequently visited pages by tourists and there were 45 valid keywords found in the website panelboard. This study is the first to examine the possibility of developing a digital surveillance system using mobile phones directly involving travelers at destinations.